Development of a virtual reality environment for human-powered vehicle simulation - Tian, Ming Hui. (2008)
Virtual environment is important for a virtual reality simulator. The overall aim of this project is to develop a real-time interactive virtual environment for a virtual bicycling simulator. This system can be used for vehicle prototyping, experiment of different models of vehicles, training and entertainment.